Determinants of purchasing behavior towards organic food among working women in Putrajaya - Nasruddin, Nurul Shazwani; Md Jusoh, Zuroni (Malaysian Consumer and Family Economics Association (MACFEA), 2023)
The green concept and green foods are developing and are still in their infancy in Malaysia. The objective of this study is to examine the relationship between determinants of purchasing behaviour and the behavior to purchase organic food among working women in Putrajaya. A total of 250 respondents at Putrajaya were involved in this study through purposive sampling using quantitative techniques through a questionnaire. Data obtained were analysed using SPSS software version 25. The Pearson Correlation Test is used to examine the relationship between two variables. The findings show that there is a significant relationship between health and nutrition and behavior to purchase organic food (r = 0.673**, p = 0.001), the significant relationship between awareness about the environment and behaviour to purchase organic food (r = 0.815 **, p = 0.000) and also there is a significant relationship between willingness to pay and behavior to purchase organic food (r = 0.815 **, p = 0.001). To conclude, only three variables are a significant relationship with the behaviour to purchase organic food. Therefore, as today's most relevant focus group, the government should educate young people about the health and environmental benefits of organic foods. In reality, the health and environmental issues of young clients are not understood, so a marketing campaign can be planned to develop a good consumer perception of organic foods and to establish a plan for active consuming organic food.